PENGEMBANGAN PRODUCT AWARENESS DAN PEMASARAN DIGITAL PADA UMKM ENTING-ENTING GEPUK “CAP DUA POHON KELAPA” SALATIGA - Yanuar Surya Putra; Setya Aji Pratama (ABDI MAKARTI, 2022)
SMEs have an important role in economic development, both nationally and on a regional scale. One of the local SMEs in Salatiga that produce enting – enting gepuk as one of the local unique foods of Salatiga is called SMEs “dua pohon kelapa”. These SMEs are faced with the branding issue. They do not understand the importance of branding in their business, brands are only considered as images or logos that show the identity of a product. In fact, a brand can be said to have the same value as a reputation. In addition, these SMEs have not maximized their digital marketing, due to a lack of understanding of digital marketing, which is currently one of the most important marketing strategies for SMEs. The method used to achieve the goal of community service is mentoring, presentation, and consultation. The target audience of this activity is the owner and employees of SMEs “dua pohon kelapa”. As a result of this service community, the owners and employees of the SMEs have an understanding of the importance of the brand as a competitive strategy and have social media accounts such as Facebook and Instagram as a tool for digital marketing.